Peningkatan Kemampuan Membaca Permulaan Siswa Kelas I SD Negeri 10 Palangka Melalui Media Kartu Huruf - Priskila Susanti (Institute For Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
This study aims to determine the increase in student learning outcomes in learning Indonesian class I after using the Card media and the increase in student learning outcomes in learning Indonesian course I after using the Letter Card media. The research used is Classroom Action Research. The subjects of this research are the first-grade students of SD Negeri 10 Palangka. The total number of research subjects is ten students. This assessment concludes that the Learning Model with the Letter Card Media method can increase the value of student learning outcomes in Indonesian language subjects in class I SD Negeri 10Palangka. II it can be concluded that the actions taken have been maximal. Students feel happy and enthusiastic in learning because, with exciting media, children do not feel bored in learning activities such as playing activities. Most students can read letters, syllables, words, and simple sentences fluently and use correct pronunciation.